Systematic comparison study on determination of small organics/polymer miscibility. (November 2020) - Zhu, Zhengxi; Yang, Haibin; Wang, Li; Mao, Shenwei; Jiang, Tao; Zhu, Peizhi; Wanyan, Qianru; Duan, Mengting
Abstract: A mixture system of small molecular organics/polymer is widely applied in various industries. A relatively accurate determination of their miscibility is crucial for well understanding and predicting their phase behaviors and material properties. However, miscibility results from different literature could vary much. This study systematically compares various approaches to determine the mixture miscibility, e.g., the interaction parameter ( χ ), solubility, observations of the phase separation, and a deviation of glass transition temperature ( T g ) or melting temperature ( T m ), and demonstrates the advantages, disadvantages, general suitability of each method. Four botanical organics, i.e., β-carotene, betulinic acid, astaxanthin, and curcumin, are used as model small molecular compounds. A widely-used, noncrystallizable, hydrophobic polymer of poly (lactic- co -glycolic acid) (PLGA, LA:GA = 55:45) is employed as a model polymer. This systematic comparison is expected to provide a guide to selecting a suitable determination of small organics/polymer miscibility, beneficial for better predicting the phase stability of an amorphous mixture in applications. Highlights: Various approaches to determine miscibility are systematically compared. Four small organics and an amorphous polymer are employed. Dynamics of phase separation is minimized by using a polymer with low T g . Advantages, disadvantages, and suitability of each approach are presented. A guide to selecting a suitable determination of miscibility is provided.